Effect of Changes in the Composition of Cellular Fatty Acids on Membrane Fluidity of Rhodobacter sphaeroides - Kim, Eui-Jin; Lee, Jeong K. (Journal of microbiology and biotechnology, 2015)
The cellular fatty acid composition is important for metabolic plasticity in Rhodobacter sphaeroides. We explored the effects of changing the cellular ratio of unsaturated fatty acids (UFAs) to saturated fatty acids (SFAs) in R. sphaeroides by overexpressing several key fatty acid biosynthetic enzymes through the use of expression plasmid pRK415. Bacteria containing the plasmid pRKfabI1 with the fabI1 gene that encodes enoyl-acyl carrier protein (ACP) reductase showed a reduction in the cellular UFA to SFA ratio from 4 (80% UFA) to 2 (65% UFA) and had decreased membrane fluidity and reduced cell growth. Additionally, the ratio of UFA to SFA of the chromatophore vesicles from pRKfabI1 -containing cells was similarly lowered, and the cell had decreased levels of light-harvesting complexes, but no change in intracytoplasmic membrane (ICM) content or photosynthetic (PS) gene expression. Both inhibition of enoyl- ACP reductase with diazaborine and addition of exogenous UFA restored membrane fluidity, cell growth, and the UFA to SFA ratio to wild-type levels in this strain. R. sphaeroides containing the pRKfabB plasmid with the fabB gene that encodes the enzyme β-ketoacyl-ACP synthase I exhibited an increased UFA to SFA ratio from 4 (80% UFA) to 9 (90% UFA), but showed no change in membrane fluidity or growth rate relative to control cells. Thus, membrane fluidity in R. sphaeroides remains fairly unchanged when membrane UFA levels are between 80% and 90%, whereas membrane fluidity, cell growth, and cellular composition are affected when UFA levels are below 80%.